The Grandmothers’ Farewell to Childcare Provision under China’s Two-Child Policy: Evidence from Guangzhou Middle-Class Families - Zhong, Xiaohui (Social Inclusion, 2020)
As China’s one-child policy is replaced by the two-child policy, young Chinese women and their spouses are increasingly concerned about who will take care of the ‘second child.’ Due to the absence of public childcare services and the rising cost of privatised care services in China, childcare provision mainly relies on families, such that working women’s choices of childbirth, childcare and employment are heavily constrained. To deal with structural barriers, young urban mothers mobilise grandmothers as joint caregivers. Based on interviews with Guangzhou middle-class families, this study examines the impact of childcare policy reform since 1978 on childbirth and childcare choices of women. It illustrates the longstanding contributions and struggles of women, particularly grandmothers, engaged in childcare. It also shows that intergenerational parenting involves a set of practices of intergenerational intimacy embedded in material conditions, practical acts of care, moral values and power dynamics. We argue that the liberation, to some extent, of young Chinese mothers from childcare is at the expense of considerable unpaid care work from grandmothers rather than being driven by increased public care services and improved gender equality in domestic labour. Given the significant stress and seriously constrained choices in later life that childcare imposes, grandmothers now become reluctant to help rear a second grandchild. This situation calls for changes in family policies to increase the supply of affordable and good-quality childcare services, enhance job security in the labour market, provide supportive services to grandmothers and, most importantly, prioritise the wellbeing of women and families over national goals.